Why Bad News Can Be Good News: The Signaling Feedback Effect of Negative Media Coverage of Corporate Irresponsibility. (March 2023) - Fu, Limin
Can bad news also be good news? In this study, I explicate why bad news about firms' corporate social irresponsibility (CSiR) can be good news for firms. Specifically, I address the role of negative media coverage of CSiR in firms' corporate social performance (CSP). Drawing on signaling theory, I propose that negative media coverage of CSiR is a form of costly yet effective external feedback to firms' current social signaling. It, therefore, propels firms to undertake organizational changes to send positive response signals through improved CSP. Furthermore, I argue that this effect is augmented by organizational innovation search, which influences firms' learning capacity required to improve firms' CSP. Using a multicountry sample of 1, 049 firms between 2007 and 2016, I find that negative media coverage of CSiR induces firms to enhance CSP, and this effect is moderated by organizational innovation search.